2018
DOI: 10.2174/1381612824666180629111632
|View full text |Cite
|
Sign up to set email alerts
|

Process Analytical Technology for Crystallization of Active Pharmaceutical Ingredients

Abstract: Application of PAT in crystallization of APIs facilitates development of robust processes that works within the design space to produce the drug products of consistent quality. Furthermore, it opens up the opportunities for continuous improvement of the process by generating knowledge base of existing processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 95 publications
0
10
0
Order By: Relevance
“…The above‐mentioned properties determine not only the quality of the final medicine product but also the efficiency of the downstream operations, such as filtration, drying, and pharmaceutical manufacturing processes, e.g., tableting. The solubility and dissolution rate are key factors that may influence the bioavailability of the API .…”
Section: Introductionmentioning
confidence: 98%
“…The above‐mentioned properties determine not only the quality of the final medicine product but also the efficiency of the downstream operations, such as filtration, drying, and pharmaceutical manufacturing processes, e.g., tableting. The solubility and dissolution rate are key factors that may influence the bioavailability of the API .…”
Section: Introductionmentioning
confidence: 98%
“…Both are important parameters in solution crystallization processes. 18,23,24,30,39,47 In the presented study, three different batch cooling crystallization experiments were adapted from the literature focused on the evaluation of a Raman spectrometer using flufenamic acid (FFA) as the model compound. 20 Today, Raman spectroscopy is an established PAT in research and development and manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the CCSA combines four LED wavelengths, spanning the ultraviolet (UV) and near-infrared (NIR) region (280, 340, 600, 860 nm), and temperature measuring capabilities (thermocouple type R) in a 380 × 30 mm housing (length × diameter, 7 mm diameter at the probe head). , Our previous study demonstrated that the CCSA can accurately measure solution and suspension concentration in aqueous formulations. Both are important parameters in solution crystallization processes. ,,,,, …”
Section: Introductionmentioning
confidence: 99%
“…Crystallization is a widely used purification technique for the manufacturing of active pharmaceutical ingredients (APIs) as well as intermediates. Crystallization as the final step in the manufacturing of APIs plays an important role in obtaining the desired critical quality attributes of APIs, which are very important for subsequent formulation processes and the performance of the final drug products . The critical quality attributes of APIs that are important to drug product performance include the chemical purity, optical purity, solid form (crystalline or amorphous), particle size, and particle shape.…”
Section: Introductionmentioning
confidence: 99%
“…Crystallization as the final step in the manufacturing of APIs plays an important role in obtaining the desired critical quality attributes of APIs, which are very important for subsequent formulation processes and the performance of the final drug products. 1 The critical quality attributes of APIs that are important to drug product performance include the chemical purity, optical purity, solid form (crystalline or amorphous), particle size, and particle shape. Generally, the amorphous form of APIs exhibits better dissolution properties, which are important to achieving high bioavailability for drugs with low aqueous solubility.…”
Section: Introductionmentioning
confidence: 99%